Homopolymer Adsorption on Hexagonal Surfaces: A Replica-Exchange Monte Carlo Study. (January 2016) - Liewehr, B; Bachmann, M
Abstract: The adsorption behavior and thermodynamic properties of a coarse-grained flexible homopolymer, grafted on a hexagonal patterned surface, are investigated by means of parallel-tempering replica-exchange Monte Carlo simulations. In this study, the strength of the polymer-surface interaction, which is based on a standard Lennard-Jones potential, is changed systematically, mimicking different honeycomb-structured substrate materials. Utilizing specific order parameters, measured over a range of various temperatures and surface adsorption strengths, different structural phases are discriminated into classes of expanded, globular, droplet, and compact conformations. Finally, we construct the hyperphase diagram for a polymer with 55 monomers and discuss representative polymer structures.